RELIGIOUS MODERATION FOR INDONESIAN MUSLIMS IN DIASPORA: The Pojok Moderasi Beragama of the Indonesian School in Riyadh, Saudi Arabia - Rohman, Fathur; Shobirin, Ma'as (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2024)
This article deals with the establishment of the Pojok Moderasi Beragama at the Indonesian School in Riyadh, Saudi Arabia, as part of its efforts to promote religious moderation among the Indonesian diaspora in the region. The initiative is driven by concerns over the vulnerability of the diaspora community to radical Islamic ideologies, such as Wahhabism and other transnational Islamic movements prevalent in the Middle East. As such, the establishment of the Pojok Moderasi Beragama at the Indonesian School in Riyadh represents a strategic preventive measure. Employing an Asset-Based Community Development (ABCD) approach, this article explores the implementation of “moderate” programs aimed at establishing the Pojok Moderasi Beragama. Initially, all teachers underwent comprehensive training to enhance their understanding of religious moderation and its practical application in the school setting. Simultaneously, mentoring activities facilitated the gradual development of religious moderation, ultimately leading to the creation of the Pojok Moderasi Beragama by leveraging the school’s existing assets. This article argues that teachers have significantly improved their understanding of religious moderation, encompassing pluralism, tolerance, and interfaith dialogue. Furthermore, it captures the progressive development of the Pojok Moderasi Beragama, which effectively utilizes the school’s resources, including the library, school website, and social media platforms.